The protective role of father behaviour in the relationship between maternal postnatal depression and child mental health - Alex F. Martin; Barbara Maughan; Matt Jaquiery; Edward D. Barker (Wiley, 2022)
Abstract Background Maternal depression, especially when severe and long‐lasting, is associated with adverse mental health outcomes in children. We aimed to assess, for children of mothers with persistent postnatal depression symptoms, whether positive father behaviours would decrease risk for conduct and emotional symptoms. Methods Using data from 4009, mother-father-child trios from the Avon Longitudinal Study of Parents and Children we examined associations between maternal depression trajectories and positive father behavioural profiles across the postnatal period (child age: 2-21 months), and child conduct and emotional symptom trajectories across middle childhood (child age: 3.5-11 years). Results Positive father behaviour was much less common in families where mothers experienced high‐persistent depression symptoms (33%) than in families where mothers did not (56%); of note, these fathers also had higher levels of depression symptoms. Using person‐level analysis, exposure to high‐persistent maternal depression symptoms increased child risk for a high trajectory of both conduct (odds ratio, 2.69; 95% CI: 2.00, 3.60) and emotional symptoms (odds ratio, 2.47; 95% CI: 1.83, 3.31). However, positive father behaviour (toward child and mother) reduced the odds of following high trajectories of conduct symptoms by 9% (x = 4.52, p < .001) and of emotional symptoms by 10% (x = 4.12, p < .001), even after controlling for father depression symptoms. Using variable‐level analysis, we did not identify an interaction between maternal depression and positive father behaviour. For conduct problems, we identified a direct effect of positive father behaviour and lower conduct problems. For emotional symptoms, father behaviour interacted with child age, where the largest decrease was seen at age 9, when symptoms were highest across the sample. Conclusions Positive father behaviour can be protective against chronic mental health problems for children exposed to persistent maternal postnatal depression symptoms.